Distribution of Araceae and the Diversity of Life Forms - Thomas B. Croat; Orlando O. Ortiz (Acta Societatis Botanicorum Poloniae, 2020)
This paper discusses the family Araceae, emphasizing its worldwide distribution and the diversity of morphological and ecological characteristics of the family that have enabled it to reach such a prominent position with diverse habitats. Few families of its size have come to inhabit such a diverse spectrum of habits and biomes. The family has important habit forms and growth structures that have enabled such distributional patterns. The very broad spectrum of life forms it demonstrates is one of the main characteristics of the family, namely broad habitat diversity. This coupled with high species diversity; high rates of endemism and the presence of large numbers of unknown species (probably the highest of any family percentage-wise) constitute principal characteristics of the family.